Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae) - Chiquetto-Machado, Pedro I.; Hennemann, Frank H.; Conle, Oskar V. (Zootaxa, 2018)
The neotropical genus of stick insects, Phantasca Redtenbacher, 1906, was recently revised by Hennemann et al. (2018). However, the females and eggs of several species remain unknown, including all five species recorded from Brazil. The female and egg of Phantasca phantasma (Westwood, 1859) are here described for the first time, based on material available at the Museu de Zoologia da Universidade de São Paulo, Brazil (MZSP). A set of measurements of males is also given, in addition to the measurements of the holotype presented in Hennemann et al. (2018). This complement to the description of P. phantasma is particularly important because it is the type species of the genus (designated by Zompro, 2001), therefore providing additional grounds for future taxonomic decisions involving Phantasca.